Analogs of Generalized Resolvents for Relations Generated by a Pair of Differential Operator Expressions One of which Depends on Spectral Parameter in Nonlinear Manner - Khrabustovskyi, V. (Журнал математической физики, анализа, геометрии, 2013)
For the relations generated by a pair of differential operator expressions one of which depends on the spectral parameter in the Nevanlinna manner we construct the analogs of the generalized resolvents which are integro-differential operators. Для отношений, порожденных парой дифференциальных операторных выражений, одно из которых зависит от спектрального параметра неванлиновским образом, построены аналоги обобщенных резольвент, которые являются интегро-дифференциальными операторами.